PENGARUH ANTARA POWER LENGAN, AKURASI DAN KOORDINASI MATA TANGAN TERHADAP KEBERHASILAN 3 POINT SHOOT PADA ATLET PUTRI BOLABASKET SKO RAGUNAN - Margono Margono; Rani Agra Berta Yagusta; Amat Khuzaini (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2018)
Abstract, This study aims to know about the influence between 2 (two) exogenous variables that will be studied its influence on endogenous variables. Endogenous variable (End1) is Accuracy (X2) endogen (End2) that is 3 Point Shoot (Y). Exogenous variables include Power Arm (X1), Hand Eye Coordination (X3) female athlete basketball Ragunan Sport School. The population in this study is all female athletes basketball Ragunan Sport School totaling 30 people, and the number of research samples amounted to 30 people (total sampling). Analytical technique used is path analysis approach. The results of this study conclude that: (1) There is a significant influence between Power Arm (X1) with 3 Point Shoot (Y), (2) There is significant influence between support Accuracy (X2) with 3 Point Shoot (Y), (3) There is a significant influence between Power Arm (X1) with Accuracy (X2), (5) There is a significant influence between Hand Eye Coordination (X3) with 3 Point Shoot (Y), and (6) There is a significant influence between Power Arm (X1) with Hand Eye Coordination (X3).